ChemInform Abstract: DABCO Prompted Tandem and Multicomponent Synthetic Protocol of Pyrano[2, 3‐a]acridines. Issue 26 (15th June 2016) - Satheeshkumar, Rajendran; Kaminsky, Werner; Prasad, Karnam Jayarampillai Rajendra
Abstract: Title compounds (IV) are conveniently and efficiently synthesized via three‐component reaction under mild reaction conditions.